2019
DOI: 10.18805/ijare.a-5123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and character association in pigeonpea [Cajanus cajan (L.) Millsp.] core collection

Abstract: An experiment was conducted in fifty seven pigeonpea genotypes to study the variability, correlation and path coefficient in pigeonpea at Department of Pulses, Centre for Plant Breeding and Genetics, Tamil Nadu Agricultural University, Coimbatore during kharif, 2015. The highest GCV was recorded for number of secondary branches/plant (111.73) followed by number of pods/plant (40.73). Heritability in broad sense ranged from 94.66 (pod size) to 99.93 (number of pods per plant). High genetic advance were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 2 publications
8
7
0
Order By: Relevance
“…This suggested that negligible influence of environment; hence phenotypic would be effective for these traits. These findings were in accordance with the result reported byAlaka et al (2020) andHemavathy et al (2019) for days to 50% flowering and days to maturity. Very little differences of GCV and PCV were observed for days to maturity that means genetic factors played a greater role in the expression of these traits and ample scope for improvement.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This suggested that negligible influence of environment; hence phenotypic would be effective for these traits. These findings were in accordance with the result reported byAlaka et al (2020) andHemavathy et al (2019) for days to 50% flowering and days to maturity. Very little differences of GCV and PCV were observed for days to maturity that means genetic factors played a greater role in the expression of these traits and ample scope for improvement.…”
supporting
confidence: 93%
“…in these characters. These findings are also reported byHussain et al (2021) for secondary branches per plant (28.14) and plant height (22.71),Alaka et al (2020) for secondary branches per plant (76.49) followed by seed yield per plant (45.46),Hemavathy et al (2019) for secondary branches per plant (111.73) followed by pods per plant (40.73) andSingh et al (2014) for plant height and number of branches per plant. Moderate values for GCV and PCV were reported for number of primary branches per plant (12.22 and 13.38%, respectively) followed by number of pods per plant (11.5 and 13.99 %, respectively) and seed yield (10.21 and 10.76 %, respectively) and this showed that environment has played significant role for the expression of these characters.…”
supporting
confidence: 79%
“…High estimates of heritability along with high genetic advance in both the year were reported for number of secondary branches per plant and number of pods per plant indicating the presence of additive gene action for these traits and hence selection would be effective for improvement in these traits. High heritability along with high genetic advance as per cent of mean for number of secondary branches per plant and pods per plant were also reported by Bhadru (2010) [10] and Hemavathy et al (2019) [6] .…”
Section: Variability Parameterssupporting
confidence: 64%
“…Seed yield per plant reported moderate heritability in 2017 while high heritability in 2018. The high estimates of genetic advance as percent of mean (>20%) in both the years for number of primary branches per plant, number of secondary branches per plant, number of pods per plant earlier by Hemavathy et al (2019) [6] . Moderate estimates (10-20%) of genetic advance as per cent of mean in both the year were reported by days to 50% flowering, days to maturity and 100 seed weight.…”
Section: Variability Parametersmentioning
confidence: 85%
“…The selection for such traits shows no significance.The relative difference in magnitude between GCV and PCV was very less for all the traits except for single plant yield indicating the lesser influence of environment on the expression of traits. Ranjani et al(2018), Pushpavalli et al (2018) and Hemavathy et al (2019) with high genetic advance as per cent of mean. The high heritability with high genetic advance implies additive gene action and selection for these traits leads to crop improvement.…”
Section: Resultsmentioning
confidence: 99%